Development of honey-melon flavored sports drink - Duenas, Coronel Francis M.; Azanza, Ma. Patricia V. (2001., 2001)
The study developed a honey-melon flavored sports drink. The first phase of the study with the selection and incorporation of a most acceptable honey-melon flavor concentration into a modified Gatorade-like basal medium. Results of the consumer acceptability tests showed that 0.04% honey-melon flavor was the most acceptable honey-melon flavor concentration. Consumer acceptability tests described the honey-melon flavore sports dirnk as having an ideal honey-melon aroma, ideal flavor strenght, slightly strong sweetness, ideal aftertaste, ideal odor and a general acceptability rating of neither like nor dislike. The sports drink basal medium with the most acceptable honey-melon flavor had the following physico-chemical characteristics: a pH value of 7.90, a TSS of 14.83 degree Bx and titrable acidity of 5.6x10-4 expressed as citric acid. Due to comments on the excessive sweetness of the basal medium, a low generalacceptability was recorded. The basal medium was modified by addinbg 0.0875g/l citirc acid, reducing sodium chloride content to 0.8325g/l and reducing glucose and sucrose to 60.00g and 102.00g, respectively. The modified basal medium was subjected to physico-chemical and sensory evaluation. It was described as having an almost honey-melon aroma, slightly strong floavor strenght, ideal sweetness, almost ideal degree of aftertaste and almost ideal odor. Final basal medium was given a general acceptability ratings of like moderately. The basal medium had the following physico-chemical characteristics: a pH value of 6.63, a TSS of 8.93 and %TA of 5.0x10-3 expressed as citric acid. The second phase of this study dealt with the selection and incorporation of the most acceptable honey-melon color. Results of the consumer acceptability tests showed that the honey-melon flsvored sprots drink with color 5YR 7/10 was the most acceptable. the consumer acceptability tests characterized the most acceptable honey-melon flavored sports drink with 5YR 7/10 color as having a light golden-orange color, an ideal honey-melon aroma, slightly strong honey-melon flavor strenght, ideal sweetness, slightly weak aftertaste and slightly strong odor. The general acceptability rating was like very much. The most acceptable honey-melon flavored and colored sports drink had the following physico-chemical characteristics: a pH value of 6.67, a Tss value of 9.33 and %TA of 5.6x10-3 expressed as citric acid. The third phase of this study involved quality assessment of the honey-melon flavored and light golden-orange colored sports drink. Results of the physico-chemical test for the honey-melon flavored and light golden-orange colored sports drink showed aa pH value of 6.67, a Tss value of 9.33 and %TA of 5.6x10-3 expressed as citric acid. Microbilogical examination on the honey-melon flavores and colored sports drink yielded <10 CFU/ml for both YMC and TPC. Results of acceptability tests of individuals, who are actively engaged in sports and are regular members of a fitness center, showed that attributes of sports drink including color, odor, flavor and refreshing effect were fair/almost comparable to the leading brand. The panelists also evaluated the honey-melon flavored and light golden-orange sports drink as like slightly. The fourth phase of the study dealt on the cost analysis of the formulated honey-melon flavored and light golden-orange colored sports dtink. Analysis showed that the actual costs of producing the sports drink contained in a 400ml plastic bottle was PhP12.50/bottle. A 30% mark up would give a suggested retail price of PhP16.25/bottle. This would mean 27.78% savings against the leading commercial brand.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Beverages